Analyzing the Existence of the Nuduk Tumpek Uye Tradition as Local Wisdom Amid Modernization - Luh Ayu Asrini; I Gede Suwindia; Ni Luh Gede Hadriani (Research Horizon, 2026)
The rapid development of modernization has posed significant challenges to the continuity of local traditions and cultural practices in many indigenous communities. This study aims to analyze the existence of the Nuduk Tumpek Uye tradition as a form of local wisdom that persists amid modernization. The research focuses on three main aspects: the factors supporting the existence of the tradition, the forms of its preservation, and the meanings embedded in its implementation. This study employs a qualitative method using observation, in-depth interviews, and documentation techniques. The informants consist of traditional leaders, religious figures, and community members. The findings reveal that the existence of the Nuduk Tumpek Uye tradition is sustained by historical, religious, social, and cultural factors. The tradition is maintained through collective participation, the active role of traditional institutions, and intergenerational transmission of values. It is also interpreted as an expression of gratitude and respect for animals, as well as a reflection of harmony between humans, nature, and God. Therefore, the tradition not only survives as a ritual practice but also functions as a system of meaning that strengthens social solidarity and cultural identity in modern society.